Parental child feeding practices and their relationship with children’s dietary intake and weight status in Nepal - Pandey, Shrijana (J Multidiscip Healthc, 2019)
Background: Small children have less control over their dietary intake and parents have a major role to play in it. The aim of our study was to determine parental child feeding practices and their association with the weight status and dietary intake of the child. Design and methods: A cross-sectional study was conducted among 138 parents and preschool children attending two private schools in Kathmandu Valley, Nepal using a structured questionnaire. Parents filled in a self-report questionnaire to assess child feeding practices, perceived activity level of the child, and dietary intake at home. Child’s height and weight was measured using a standard height scale and a digital weighing scale. A digital food scale was used for measuring dietary intake. Results: Eight percent of the children were overweight and another 8% were obese. On bivariate analysis, the BMI of parents had weak, positive, and significant correlation (r=0.206, p=0.016 for fathers; r=0.307, p≤0.001 for mothers) with child’s weight status. Similarly, concern about child’s overweight had a significant, positive correlation (r=0.232, p=0.006) with the weight status of the child. Furthermore, these three independent variables were found to be significant predictors of a child’s weight status on multivariate analysis. None of the studied independent variables was associated with dietary intake. Conclusion: The study concludes that parental BMI and parental concern about the child being overweight is significantly associated with the weight status of the child.